Cover Image: Revitalized β‐form crystal during the remelting and recrystallization processes in isotactic polypropylene/glass fiber composites. Issue 1 (13th March 2020) - Qin, Yijing; Zhang, Liying; Guo, Xiaobei; Dai, Kun; Schubert, Dirk W.; Zheng, Guoqiang; Liu, Chuntai
Crystalline memory effect of β‐form crystal: In iPP/glass fiber composites, the orientation of isotactic polypropylene (iPP) molecular chains induced by the shear field and the pre‐shear temperature simultaneously affected the thermal stability of primary sheath structure. In article e10008, Yijing Qin and colleagues examined theeffects of remelting and recrystallization processes in iPP composites on the formation of β‐form crystals. During tens of remelting and recrystallization processes, some crystal nuclei ofβ‐form crystals could "revitalize" continuously or fitfully. Moreover, some new nucleation sitesof β‐form crystals appeared from the second recrystallization process. The findings preliminarily indicated that the "crystalline memory effect" of β‐form crystal might depend not only on the orientation level of molecular chains of sheath structure, but also on the spatial arrangement of fibrillar lamellae in sheath structure. (DOI: 10.1002/PCR2.10008 )